Childhood Trauma and Hippocampal and Amygdalar Volumes in First-Episode Psychosis - Hoy, Katrina (Oxford University Press, 2012)
Objective: A history of childhood trauma is common in individuals who later develop psychosis. Similar neuroanatomical abnormalities are observed in people who have been exposed to childhood trauma and people with psychosis. However, the relationship between childhood trauma and such abnormalities in psychosis has not been investigated. This study aimed to explore the association between the experience of childhood trauma and hippocampal and amygdalar volumes in a first-episode psychosis (FEP) population. Methods: The study employed an observational retrospective design. Twenty-one individuals, who had previously undergone magnetic resonance imaging procedures as part of the longitudinal Northern Ireland First-Episode Psychosis Study, completed measures assessing traumatic experiences and were included in the analysis. Data were subject to correlation analyses (r and r (pb)). Potential confounding variables (age at FEP and delay to scan from recruitment) were selected a priori for inclusion in multiple regression analyses. Results: There was a high prevalence of lifetime (95%) and childhood (76%) trauma in the sample. The experience of childhood trauma was a significant predictor of left hippocampal volume, although age at FEP also significantly contributed to this model. There was no significant association between predictor variables and right hippocampal volume. The experience of childhood trauma was a significant predictor of right and total amygdalar volumes and the hippocampal/amygdalar complex volume as a whole. Conclusions: The findings indicate that childhood trauma is associated with neuroanatomical measures in FEP. Future research controlling for childhood traumatic experiences may contribute to explaining brain morphology in people with psychosis.